Static Balancing of Wheeled-legged Hexapod Robots - Daniele Cafolla (Robotics, 2020)
Locomotion over different terrain types, whether flat or uneven, is very important for a wide range of service operations in robotics. Potential applications range from surveillance, rescue, or hospital assistance. Wheeled-legged hexapod robots have been designed to solve these locomotion tasks. Given the wide range of feasible operations, one of the key operation planning issues is related to the robot balancing during motion tasks. Usually this problem is related with the pose of the robot’s center of mass, which can be addressed using different mathematical techniques. This paper proposes a new practical technique for balancing wheeled-legged hexapod robots, where a Biodex Balance System model SD (for static & dynamic) is used to obtain the effective position of the center of mass, thus it can be recalculated to its optimal position. Experimental tests are carried out to evaluate the effectiveness of this technique and modify and improve the position of hexapod robots’ center of mass.